Nearly found - Casimano, Elle. (New York, N.Y. : Penguin Group, 2015)
High School senior and science whiz Nearly Boswell, called Leigh, is thrilled when she gets an internship in forensic science lab, since it is a step toward college and a way out of the trailer park - but soon she finds herself the target of a serial killer, one who seems to know a lot about residents of Sunny View Trailer Park as well as her absent father's secrets.
Keywords: Criminal investigation -- Juvenile fiction; Murder -- Juvenile fiction; Serial murderers -- Juvenile fiction